Enhancing the EFL Students’ Achievement in Writing Descriptive Text through Think-Pair-Share - Sanjaya, Dedi; Agustina, Lia (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2019)
The purpose of tis study was to investigate English as Foreign Language (EFL) students’ achievement in writing skill (descriptive text) through Think Pair Share method. Therefore, the action research design was implemented to match with the purpose of the study. The techniques of collecting the data were writing test, observation, questionnaire, and interview. The result of the study shows that the students’ achievement sustainably improved from the first evaluation, which was 65,50 to second evaluation, which was 75,09 and to the third evaluation, which was 85,50. The score continuously improved from the first evaluation to the third evaluation. Observation result shows that the students gave their good attitudes and responses during teaching and learning process by applying the application of TPS (Think Pair Share) method. Questionnaire and interview report shows that students agreed that the application of TPS (Think Pair Share) method had helped them in writing descriptive text. In conclusion, the application of TPS method significantly improved students’ achievement in writing descriptive text